Effect of yoga on the quality of life of patients with rheumatic diseases: Systematic review with meta-analysis - Sieczkowska S.M.* (2019)
© 2019 Elsevier LtdAim: To analyze the effects of yoga on the quality of life of patients with rheumatic diseases through a systematic review with meta-analysis. Methods: This systematic review with meta-analysis was conducted following the recommendations of the Declaration of PRISMA. The searches were carried out on the databases PubMed, Web of Science, EBSCO, Scopus, and Cochrane until August 2018. Experimental studies evaluating the effect of yoga on the quality of life in patients with rheumatic diseases were included. Results: After data searches, 483 studies were found, 23 of which were included in our analysis. We found that yoga improves the overall quality of life (d= −0.64; 95% CI: −0.91 to 0.038) of patients with rheumatic diseases, as well as the following domains: functional capacity (d = 16.43; 95% CI: 13.37–19.49), physical aspects (d = 27.11; 95% CI: 19.40–34.83), emotional aspects (d = 26.00; 95% CI: 18.87–33.13), general health (d = 16.61; 95% CI: 12.66–20.55), and social aspects (d = 7.01; 95% CI: 5.57–9.45). Conclusion: Evidence suggests weak recommendations can be made for the use of yoga in the management of RD patients.